Investigating the information behavior of chess student-athletes at UP Diliman with implications for self-training: needs, sources, motivations, and challenges - Bunao, Katherine T.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
The importance of information cannot be overstated, as it is consistently gathered, scrutinized, and applied across various contexts. For student-athletes, the ability to seek, process, and apply relevant information is crucial for both their academic and athletic success. However, there is minimal literature that specifically explores their athletic training aspects, making this study vital.

The study focuses on the information needs and information-seeking behavior of chess student-athletes at the University of the Philippines Diliman, with a particular focus on their self-training. Chess, a sport that demands strategic thinking and continuous learning, places unique information demands on its players. Understanding how these student-athletes seek utilize information can help to better support their development and performance.

Utilizing a qualitative approach, and research delved into how the student-athletes seek, process, and apply information to enhance their chess skills. By conducting focus group discussions with members of the Diliman Chess Team, the study examined the nature of their information needs preferred sources, evaluate methods and underlying motivations in pursuing information. Key challenges were also identified that included accessibility issues, information overload, and financial constraints. The research also highlighted adaptive strategies employed by the student-athletes to overcome these barriers, such as consulting coaches and teammates, taking strategic breaks, and seeking alternative resources.

The findings emphasized the importance of providing accessible, credible, and relevant resources and tailored information services to support the continuous development of chess student-athletes specially in their athletic endeavors.
Thesis
Keywords: University of the Philippines (Diliman).; Information behavior; Chess players; College athletes